Educational stock and economic growth The case of Greece over the period 1981-2009 - Pegkas, Panagiotis (SPOUDAI Journal of Economics and Business, 2012)
This paper examines the impact of education on economic growth in Greece over the period 1981 – 2009 by applying the model with two sectors introduced by Lucas (1988). The findings of the empirical analysis reveal that there is no long-run relation between educational stock and output. In the short run educational stock has had a statistically insignificant negative effect on economic growth. The econometric model explained 64% up to 72% of the variation of the economic growth rate through the variation of the independent variables. By checking the assumption of scale returns of the model, the results showed that the human capital stock grows but at a decreasing rate, so the endogenous character of the economic growth is not verified. JEL classification: O40, O41, O47, I21, I25